Pembinaan, kesahan dan kebolehpercayaan modul bimbingan terapi realiti teori pilihan - Idris, Adawiah; Shaari, Azemi (UUM Press, 2017)
This study aims to develop Choice Theory Reality Therapy Module. In addition, it is also to determine the validity and the reliability of the module in order to reduce the negative behavior of students in the classroom. The development of this module is based on Sidek Model Development Module (SMDM) and Choice Theory Reality Therapy. The design of this study is descriptive study Three module experts and Reality Therapy experts were selected which is all had a Doctoral Degree in counseling and psychology. The instrument used for the validity of the module created by Jamaludin Ahmad (2002). Alpha Cronbach module validity is .80. Meanwhile, a group of twenty students who got the highest score for the Assessment of Behavioral Disaffection was selected for the reliability of this module. Alpha Cronbach module reliability is .90. Since the literature review finds the effectiveness of Reality Therapy, it is suggested that the use of the Reality Therapy thoroughly which is the Want, Doing, Evaluate, Planning to be apply in individual counseling, groups counseling or guidance modules